Militias in the Chilean October: The Front Line of Protest; [Milicias en el Octubre Chileno: La Primera Línea de la Protesta] - Santos-Herceg, J (Universitat de Valencia, Faculty of Philology, Translation and Communication, 2024)
This text seeks to argue that the First Line, which was deployed during the Social Outbreak in Chile, can be conceived as a Militia and its participants as militiamen. It is intended to show that, although it has particular characteristics, it shares essential elements with the classic medieval militias. With this objective in mind, the text focuses on the following characteristics of the First Line. First, the fact that it was self-convened. Secondly, it was an emergent phenomenon in both senses (abrupt emergence and imperative necessity). Thirdly, in the fact that it was ephemeral. Fourthly, in that the need to which it responds with its emergence is fundamentally defensive. Fifthly, in that its constitution is extremely diverse (diverse participants, diverse forms of participation). Finally, it is an eminently belligerent structure. © 2024 Universitat de Valencia, Faculty of Philology, Translation and Communication. All rights reserved.